AN IMPLEMENTATION OF STRATEGY TRAINING IN TOEFL LISTENING CLASS: Case Study in One Language Center in Bandung - Perdani, Yella Dezas (2015)
Taking TOEFL test is one of the graduation requirements for non-English learners. Nevertheless, some of the learners still face difficulties in answering the test, especially on the listening section as it is regarded as the most difficult one for non-English learners. Because of that reason, the learners need to join strategy training program in order to learn the appropriate strategy to answer TOEFL listening questions. Thus, this research was carried out to investigate the strategies trained by the instructor of the TOEFL listening section in teaching non-English University learners, the way the strategies trained and the effects of those strategies on the learners' listening ability as an attempt to help the learners to cope with their difficulties. By employing largely a descriptive qualitative research, this study was conducted at one language center in Bandung, West Java, involving the instructor of the listening TOEFL section and 25 learners enrolling in his class. The data were collected through observation, interview, questionnaire and pre-test post test result. An eight-meeting observation was carried out in two months. The interviews were addressed to both the instructor and four of his learners. The questionnaire was distributed to all of the learners. And the result of pre-test and post-test were measured by using t-test. The results of this research show that there are 22 strategies trained by the instructor which are effective in helping learners to choose the right answers in the TOEFL listening section. Among the 22 strategies, 17 strategies were found in part A, and 5 others were found in part B and part C. There are three stages conducted by the instructor in applying strategy training; pre-teaching, whilst-teaching and post-teaching. The results further reveal that the strategies improve the learners' listening ability and their TOEFL score, especially in the listening section; familiar with the strategies of TOEFL listening and can apply it; familiar with english text; and enjoy english more which encourages them to use English for communication. Mengikuti tes TOEFL adalah salah satu persyaratan bagi mahasiswa non-bahasa Inggris. Namun begitu, sebahagian mahasiswa masih menghadapi kesulitan dalam menjawab soal-soal pada tes tersebut, khususnya pada sesi menyimak yang diketahui sebagai sesi tersulit bagi mahasiswa non-bahasa Inggris. Karena alasan tersebut, mahasiswa perlu mengikuti program strategi training untuk mempelajari strategi dalam menjawab pertanyaan pada sesi menyimak. Dengan demikian, penelitian ini ini dilakukan untuk menginvestigasi strategi yang di ajarkan oleh instruktur TOEFL dalam mengajarkan mahasiswa non-bahasa Inggris, cara strategi tersebut di ajarkan, dan efek dari strategi tersebut pada kemampuan menyimak mahasiswa. Dengan melaksanakan peneliatian kualitatif, penelitian ini dilaksanakan disalah satu Balai Bahasa di Bandung, Jawa Barat, melibatkan instruktur dari TOEFL dan 25 orang mahasiswa yang mengikuti kelasnya. Data dikumpulkan melalui observasi, wawancara, angket, dan hasil pre tes dan post test. Delapan pertemuan diobservasi selama dua bulan. Wawancaea diajukan kepada instruktur dan empat orang mahasiswa. Angket diberikan kepada semua mahasiswa. Dan hasil pre test dan post tes dihitung dengan menggunakan t-tes. Hasil dari penelitian ini menunjukkan ada 22 strategi yang diajarkan yang efektif dalam membantu mahasiswa dalma menjawab pertanyaan menyimak TOEFL, ada 17 strategi untuk sesi A dan 5 strategi untuk sesi B dan C. Ada tiga tahap pengajaran yang dilakukan oleh instruktur, pre-teaching, whislt-teaching dan post-teaching. hasil penelitian menunjukkan bahwa strategi yang di ajarkan meningkatkan kemampuan menyimah mahasiswa, mereka menjadi familiar dengan strategi dalam menjawab pertanyaan menyimak TOEFL, dan mereka juga menyukai bahasa Inggris sehingga mendorong mereka dalam menggunakan bahasa inggris lebih sering.